Confinement of Dyes inside Boron Nitride Nanotubes: Photostable and Shifted Fluorescence down to the Near Infrared. Issue 29 (2nd June 2020) - Allard, Charlotte; Schué, Léonard; Fossard, Frédéric; Recher, Gaëlle; Nascimento, Rafaella; Flahaut, Emmanuel; Loiseau, Annick; Desjardins, Patrick; Martel, Richard; Gaufrès, Etienne
Abstract: Fluorescence is ubiquitous in life science and used in many fields of research ranging from ecology to medicine. Among the most common fluorogenic compounds, dyes are being exploited in bioimaging for their outstanding optical properties from UV down to the near IR (NIR). However, dye molecules are often toxic to living organisms and photodegradable, which limits the time window for in vivo experiments. Here, it is demonstrated that organic dye molecules are passivated and photostable when they are encapsulated inside a boron nitride nanotube (dyes@BNNT). The results show that the BNNTs drive an aggregation of the encapsulated dyes, which induces a redshifted fluorescence from visible to NIR‐II. The fluorescence remains strong and stable, exempt of bleaching and blinking, over a time scale longer than that of free dyes by more than 10 4 . This passivation also reduces the toxicity of the dyes and induces exceptional chemical robustness, even in harsh conditions. These properties are highlighted in bioimaging where the dyes@BNNT nanohybrids are used as fluorescent nanoprobes for in vivo monitoring of Daphnia Pulex microorganisms and for diffusion tracking on human hepatoblastoma cells with two‐photon imaging. Abstract : Templating fluorescent dyes into specific aggregation states using dye encapsulation into small‐diameter boron nitride nanotubes (dyes@BNNT), the concept of a luminescent hybrid nanomaterial exhibiting bright emission, low toxicity, and resistance to chemical degradation and photobleaching is unlocked. The dyes@BNNTs are used in the design of multimodal nanoprobes for bioimaging in a wide optical range from visible to near infrared.